2014
DOI: 10.1002/ange.201400575
|View full text |Cite
|
Sign up to set email alerts
|

Counting of Oxygen Defects versus Metal Surface Sites in Methanol Synthesis Catalysts by Different Probe Molecules

Abstract: Different surface sites of solid catalysts are usually quantified by dedicated chemisorption techniques from the adsorption capacity of probe molecules, assuming they specifically react with unique sites. In case of methanol synthesis catalysts, the Cu surface area is one of the crucial parameters in catalyst design and was for over 25 years commonly determined using diluted N2O. To disentangle the influence of the catalyst components, different model catalysts were prepared and characterized using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 36 publications
(26 reference statements)
1
29
0
Order By: Relevance
“…Although the TEM imaging shows almost complete surface coverage of Cu particles, the accessibility of the Cu surface is still unclear due to the fact that only 2D projections are indicated in TEM imaging. Fichtl et al [25] concluded that about 30% of the Cu surface area is accessible based on H2-temperature programed reduction (H2-TPD) results. Lunkenbein et al [24] argued that these results discredit the direct correlation between catalyst activity and surface area.…”
Section: Copper-based Catalystsmentioning
confidence: 99%
“…Although the TEM imaging shows almost complete surface coverage of Cu particles, the accessibility of the Cu surface is still unclear due to the fact that only 2D projections are indicated in TEM imaging. Fichtl et al [25] concluded that about 30% of the Cu surface area is accessible based on H2-temperature programed reduction (H2-TPD) results. Lunkenbein et al [24] argued that these results discredit the direct correlation between catalyst activity and surface area.…”
Section: Copper-based Catalystsmentioning
confidence: 99%
“…4 shows the H 2 -TPD spectrum and corresponding modelling result for a high performance Cu/ZnO/Al 2 O 3 catalyst presented in Ref. [4]. Although the catalyst clearly exhibits an at least In both models a fixed prefactor of k 0,des = 3.75 9 10 10 s -1 is used Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Especially the N 2 O-RFC is widely employed due to its simplicity and fast measuring process. Although recent results showed that the application of N 2 O-RFC in typical Cu/ZnO/Al 2 O 3 systems does not only oxidize the copper surface, but also oxygen defect sites generated at the Cu/ZnO interface, a linear relationship between activity and N 2 O adsorption capacity can often be established for catalysts with similar preparation history [3][4][5]. In contrast, the H 2 -TPD method only describes the exposed copper surface area, but suffers from a more challenging experimental effort as the dissociative adsorption of hydrogen on copper is an activated process and full coverage is only achieved at low temperatures using elevated pressure or predecomposed atomic hydrogen [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The long-known ''synergy'' [102][103][104][105] between Cu and its ''support'' ZnO leads to active sites comprising Cu, Zn and oxygen in unknown stoichiometric and structural relations. We know that the active catalyst carries an overgrowth of a metastable form of ZnO [106] sitting on a copper surface that is activated by structural defects creating surface steps [107][108][109]. It is more than unlikely that such a complicated functional structure of a high-performance catalyst [110] can be described in any meaningful form by a perfect Cu metal surface model.…”
Section: The Chemical Toolbox Of Cecmentioning
confidence: 99%